Pengaruh Pengetahuan, Tingkat Pendapatan, Religiusitas, Sosialisasi, Dan Akses Media Informasi, Terhadap Intensi Berwakaf Masyarakat Muslim Di Kota Palembang - Sasmita; Jayanti, Sri Delasmi; Rosyada; Eka Nurzanah (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2024)
This research aims to find out the influence of knowledge, Income level, socialization religiosity and access to information media on the waqf intentions of muslim communities in the city of palembang. The sample used was 100 respondent from the slovin formula calculation and using the purposive. Sample sampling technique. The analysis used included instrument testing, calssical assumption tesing, multiple linear regression testing, and hypothesis testing. The results of the study partially show that knowledge has a positive and significant influence on waqf intentions, income level does not have a positive and significant influence on waqf intentions, religiosity has a positive and significant influence on waqf intentions, socialization has a positive and significant influence on waqf intentions and access to information media provide a positive and significant influence on waqf intentions. It is hoped that the research result obtained can provide benefits to the community in the city of palembang in optimizing community intention in waqf with knowledge, income level, religiosity, socialization and access to information media